Dryer laundry bag: kanso bag / Muhammad Raqib Ayub … [et al.] - Ayub, Muhammad Raqib; Ali, Nurmashitah; Abdul Aziz, Nurul Nabihah; Wan Hasan, Wan Hasmat (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The term kanso originated from a Japanese word which simply means dryness. Portability and hygiene are solely focused in the work of designing the Kanso Bag. Travellers, specifically beach goers and other water activity enthusiasts, are the targeted market for this invention. This group would be the most likely to have problem of clothes with a damp smell and this invention could assist to avoid it as well as enhance the vacation experience. Heat is a necessary element in order to dry and eliminate the damp smell from damp clothes. Thus, the heater placed in the bag will play its role by spreading heat evenly with the damp clothes sealed in the bag to trap the heat to make the drying process more effective. The interior of the bag is made from heat reflector material to enhance efficiency. Unfortunately, this laundry bag cannot accommodate the amount of clothes as the dryer does. Since portability is the main focus of this invention, the size of the bag is designed to be 32cm x 25cm with the purpose to make the heat travel faster. The time consumption for the process of drying the damp clothes would take up to 15 minutes to make approximately 10-12 damp clothes completely dry. The compact design suits potential customers' demand and people from the income group above the B40 are willing to spend money because of the stereotype toward the exclusive items and more particular in hygiene standards. However, this innovative product has many advantages to the travellers in managing clothing as well as improving the vacation experience.